Modeling of normal-state like contribution on the pinning induced magnetostriction - Inanir, F.; Okutan, M.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2008)
To describe the change of the sign of the magnetostriction at the field close to the upper critical field, B-c2, which were observed in some magnetostriction measurements carried out on the type-II superconductors, theoretical magnetostriction curves for the superconducting state were obtained considering the normal-state like contribution. The calculations were performed employing Bean, Kim, Linear, and the exponential critical-state models. We have reproduced the magnetostriction curves measured by Nabialek et al. [A. Nabialek, B. Kundys, Yu Bukhantsev, A. Wisniewski, S.M. Kazakov, J. Karpinski, H. Szymczak, Supercond. Sci. Technol. 16 (2003) 707] on MgB2 superconductors and Ikuta et al. [H. Ikuta, Y. Nakayama, N. Hirota, K. Kishio, K. Kitazawa, Appl. Supercond. 1 (1993) 635] on (La1-xSrx)(2)CuO4 superconductors, in which was observed such sign alternation, employing the exponential model. It is evaluated that inhomogeneity of the magnetic induction across the sample volume owing to the existence of critical current causes the normal-state like contribution to the flux-pinning induced magnetostriction. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Single-Crystals; Giant Magnetostriction; Superconducting State; Magnetic-Field; Induced Stress; Flux; Temperature; Transverse; Strain; Shape